Diagnosis of Tongue Cancer by MRI: Comparison of sensilivity between MRI and CT, and with histopathological finding - Asanami, Soichiro; Uchiyama, Kimio; Takamori, Koji; Tanaka, Yoichi; Iwabuchi, Hiroshi (Journal of Japanese Society of Oral Oncology, 2001)
In this study, We examined the utility of MRI diagnosis concerning the tumor extent in the primary lesion of tongue cancer in comparison with other manipulations. The subjects were 42 patients who had received a surgical intervention for S. C. C. of the tongue graded T2-T4 and examined by MRI and CT. The sensilivity by MRI was 90.9% which was significantly higher than the value by CT of 35.1%. Among T1WI, T2WI and T1Gd-DTPA, showed the highest sensilivity. As for the difference in the tumor extent indicated by MRI and by palpitation in relation to the actually resected tumor, no difference was observed between MRI and palpitation. In the histopathological finding as compared with MRI, however, MRI could recognize the shorter diameter about 40-50% and the depth about 60-70% as large as those recognized by histopathological examination.